Where did pragmatics come from ? - HAMAD, A (Journal of Human Sciences, 2003)
The present study is concerned with the early beginnings of pragmatics. It investigated the linguistic and philosophical backgrounds of this field. It was argued that pragmatics grew within philosophy and its emergence as an independent field was, for some time, delayed by the influence of some linguistic theories especially the generative-transformational theory. Finally, it was pointed out that this field was freed from the influence of this theory.